Detection and genetic diversity of porcine rotavirus A, B and C in eastern Australian piggeries. Issue 4 (18th January 2023) - Genz, B; Gerszon, J; Pollock, Y; Gleeson, B; Shankar, R; Sellars, MJ; Moser, RJ
Abstract : Rotaviruses (RV) have a high prevalence in piggeries worldwide and are one of the major pathogens causing severe diarrhoea in young pigs. RV species A, B, and C have been linked to piglet diarrhoea in Australian pig herds, but their genetic diversity has not been studied in detail. Based on sequencing of the structural viral protein 7 (VP7) RVA G genotypes G3, G4 and G5, and RVC types G1, G3, G5, and G6 have been identified in Australian piggeries in previous studies. Although occurrence of RVB was reported in Australia in 1988, no further genetic analysis has been conducted. To improve health management decisions in Australian pig herds, more information on RV prevalence and genetic diversity is needed. Here, 243 enteric samples collected from 20 pig farms within Eastern Australia were analysed for the presence of RV in different age groups using a novel PCR‐based multiplex assay (Pork MultiPath™ enteric panel). RVA, RVB, and RVC were detected in 10, 14, and 14 farms, respectively. Further sequencing of VP7 in selected RV‐positive samples revealed G genotypes G2, G5, G9 (RVA), G6, G8, G14, G16, G20 (RVB), and G1, G3, G5, G6 (RVC) present. RVA was only detected in young (<10 weeks old) pigs whereas RVB and RVC were also detected in older animals (>11 weeks old). Interestingly, RVB and RVC G‐type occurrence differed between age groups. In conclusion, this study provides new insights on the prevalence and diversity of different RV species in pig herds of Eastern Australia whilst demonstrating the ability of the Pork MultiPath™ technology to accurately differentiate between these RV species.